PHACES syndrome with Ectopia cordis - Sharma, Rambabu; Bagri, Dhan Raj; Jangid, Narendra (International Journal of Contemporary Pediatrics, 2018)
PHACES syndrome is an acronym for, P, posterior fossa anomalies as Dandy- Walker malformation; H, hemangioma (capillary segmental faces); A, arterial lesions of the head and neck (the most common ones include aberrant origin or course, hypoplasia, dysplasia and agenesis); C, cardiac abnormalities as coarctation of aorta; E, abnormalities of the eye and S, sternal defect. The constellation of findings of PHACES syndrome may vary significantly in different patients. Complete sternal cleft with ectopia cordis is an extremely rare congenital anomaly failed ventral migration and fusion of the two-lateral mesodermal sternal bands between the sixth and ninth weeks of gestation. We are reporting a rare case of PHACES syndrome, with partial ectopia cordis as a midline defect, who is in our follow up since birth. Survival of the child without surgical intervention with epithelialization over the defect and Leucomatous corneal opacity are interesting findings.